2002
DOI: 10.1590/s1516-84842002000100006
|View full text |Cite
|
Sign up to set email alerts
|

Alterações hematológicas e gravidez

Abstract: Os autores apresentam neste relato uma revisão das alterações hematológicas na gestação. Apresentam dados conhecidos da literatura como a redução dos parâmetros eritrocitários, hemoglobina e hematócrito e o aumento da produção de eritropoetina sem que ocorra alteração da massa eritrocitária em relação ao peso corporal. Descrevem as alterações leucocitárias e as alterações humorais e suas repercussões imulógicas, assim como do nível das citocinas mensuráveis em nosso organismo durante o período gestacional. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
41

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 7 publications
3
21
0
41
Order By: Relevance
“…The secretion of this circulating glycoprotein stimulates increased production of erythrocytes in the bone marrow (LURIE, 1993). This phenomenon, which has been described in pregnant rabbits (KIM, 2002) and pregnant women (SOUZA et al, 2002), has also been observed by VAZ et al (2000) in Arabian pregnant mares. According to SOUZA et al (2002), there is 40-50% an increase in blood's volume for pregnant women.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The secretion of this circulating glycoprotein stimulates increased production of erythrocytes in the bone marrow (LURIE, 1993). This phenomenon, which has been described in pregnant rabbits (KIM, 2002) and pregnant women (SOUZA et al, 2002), has also been observed by VAZ et al (2000) in Arabian pregnant mares. According to SOUZA et al (2002), there is 40-50% an increase in blood's volume for pregnant women.…”
Section: Resultssupporting
confidence: 62%
“…However, these values diminished in the two breeds during the final period of pregnancy. According to SOUZA et al (2002), fetal growth that occurs in that period of pregnancy produces a greater oxygen demand. This greater need for oxygen is Ciência Rural, v.37, n.6, nov-dez, 2007.…”
Section: Resultsmentioning
confidence: 99%
“…O aumento do volume circulatório materno é uma das mudanças fisiológicas mais marcantes durante a gravidez, o qual pode alcançar até 50% do volume pré-gestacional na trigésima semana de gestação (Souza et al, 2002). Tal condição dificulta o diagnóstico correto da anemia, uma vez que a concentração da hemoglobina é alterada pela hemodiluição em diversos graus.…”
Section: Introductionunclassified
“…This fact can partly explain the lower prevalence of anemia found in the After fortification group, considering the influence of gestational age on hemoglobin levels 3 . However, mean Hb levels did not differ in the first and second gestational trimesters.…”
Section: Discussionmentioning
confidence: 95%
“…Pregnant women represent one of the most vulnerable groups, due to the high iron requirement to meet both the mother's and the fetus' needs 3 . It is estimated that 52% of pregnant women in developing countries have anemia, whereas this proportion is 23% in developed countries 1 .…”
Section: Introductionmentioning
confidence: 99%